(untitled) (Terr@ Plural, 2023)
This study was performed with rural young women with a degree in Agronomy and Education from the Universidade Federal da Fronteira Sul (UFFS), Campus Erechim/RS. In this research, we sought to understand the participation of these women in the process of succession in family farming. We started from the hypothesis that university education could contribute to the succession in family farming, especially regarding the young agronomists. In order to develop the analysis, we work with self-declared rural women, who entered university from 2010 to 2014, aged between 15 and 29 years old. The research shows that succession results from multifactorial conditions. Therefore, university education is important, but it does not respond to succession individually. With a college degree young women could contribute in a different way to family farming, although it is necessary to review family internal relations, and the need of infrastructure and public policies oriented to a female perspective within the institution.